1984
DOI: 10.1136/hrt.52.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corwin (ICI 118587) on resting and exercise heart rate and exercise tolerance in digitalised patients with chronic atrial fibrillation.

Abstract: The effect of Corwin, a new oral beta, partial agonist, on the ventricular response to atrial fibrillation was studied in digitalised patients during 24 hour ambulatory electrocardiography and during exercise on a treadmill in a double blind placebo controlled crossover trial. Corwin reduced the maximum heart rate during exercise from 162(16) beats/min to 120(9) beats/min and reduced the peak heart rate during ambulatory electrocardiography from 113(11) to 90(6) beats/min consistent with a beta adrenoreceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Therefore, its overall effect is to stabilise sympathetic control of the heart at a level equal to the PAA [1]. In the clinical setting the stabilising effect has been characterised by a reduction in the circadian variability of heart rate [19,20]. However, conventional analysis of mean hourly heart rate is not necessarily useful for quantification of the net chronotropic effect on the diurnal average, although it can clearly illustrate the circadian prone of the effect of a drug.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its overall effect is to stabilise sympathetic control of the heart at a level equal to the PAA [1]. In the clinical setting the stabilising effect has been characterised by a reduction in the circadian variability of heart rate [19,20]. However, conventional analysis of mean hourly heart rate is not necessarily useful for quantification of the net chronotropic effect on the diurnal average, although it can clearly illustrate the circadian prone of the effect of a drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of this combination on exercise tolerance is inconsistent, with some studies reporting deterioration in exercise capacity,31–33 35 41 some improvement26 36 39 and most no change 22 24 27 28 31 34 37 40 42 44…”
Section: β-Blockersmentioning
confidence: 99%
“…The combination of xamoterol with digoxin resulted in improved exercise tolerance and also less HR variability compared with digoxin alone. Digoxin and xamoterol were used in combination in three double-blind, randomised, cross-over studies 31 34 36. Molajo et al found that this combination improved exercise tolerance and 24 h HR variability,36 but the other two reported unchanged exercise tolerance compared with digoxin.…”
Section: β-Blockersmentioning
confidence: 99%
“…Another ,B-adrenoceptor partial agonist, xamoterol, has also been shown to be effective at controlling ventricular rate in patients with atrial fibrillation (Molajo et al, 1984). Xamoterol has positive inotropic effects (James et al, 1990) and can be used in the treatment of mild heart failure (German & Austrian Xamoterol Study, 1988), it therefore offers considerable advantages over adjuvant treatment with ,B-adrenoceptor blockers in atrial fibrillation.…”
Section: Xamoterolmentioning
confidence: 99%
“…Xamoterol has positive inotropic effects (James et al, 1990) and can be used in the treatment of mild heart failure (German & Austrian Xamoterol Study, 1988), it therefore offers considerable advantages over adjuvant treatment with ,B-adrenoceptor blockers in atrial fibrillation. In a double-blind cross over study additional treatment with xamoterol 200 mg twice daily to digitalised patients reduced maximum diurnal and exercise induced heart rate, increased minimal heart rate and prolonged exercise tolerance (Molajo et al, 1984). In a more recent placebo controlled study xamoterol was given to patients with atrial fibrillation and excessive bradycardia (Ang et al, 1990).…”
Section: Xamoterolmentioning
confidence: 99%